The impact of technogenic factors on human skin cancer increase in the Odesa region - Lebedyuk, M.; Yevchev, F. (Journal of Education, Health and Sport, 2023)
It is known that malignant diseases are one of the most important medico-biological and socio-economic problems in the world and, especially, in Ukraine. Cancer is a worldwide problem; about 2.9 million new cases of the disease are registered annually in the developed countries of the world and more than 3 million in developing countries. The causes of the face skin cancer like all other malignant neoplasms are not fully established. The pesticides are known to provide a wide range of effects on the human body and, in particular, a complex of various types of biological activity - cytogenetic, carcinogenic, teratogenic, embryotoxic, etc. The main purpose of this work is to determine the consequences of agrochemicals use in 1970-1990th on the human skin malignant neoplasms incidence increase after 1990 based on the statistical indicators evaluation in the department of dermatology and in the Zonal agrochemical laboratory. The characteristics of main factors of the anthropogenic impact on the environment, abundance and residual quantity of pesticides in the geological habitat of the Odessa region were examined. According to the method of correlation analysis the relation between application of pesticides and sickness rate of the cancer of the skin of face and body. Authors conclude that Odesa region geological environment contamination with polyagrochemicals (soil cover, bottom sediments of reservoirs and watercourses, as well as groundwater) leads to toxic pollution of the biosphere and has a carcinogenic effect on the body, which ultimately leads to an increase in episodes of malignant neoplasms of the skin of the body in the Odesa region. The comparative analysis showed that the sickness rate of the cancer of skin of body in the village and urban sector is approximately equal. The uncontrolled use of pesticides from 1960 to 1990 had a negative impact on the formation of malignant neoplasms indexes in the Odesa Region, which increased significantly, especially over the last two decades.